Genome-Wide Association Study of Prognosis in Advanced Non–Small Cell Lung Cancer Patients Receiving Platinum-Based Chemotherapy - Hu, Lingmin (2012)
PURPOSE: Genetic variation may influence chemotherapy response and overall survival in cancer patients. EXPERIMENTAL DESIGN: We conducted a genome-wide scan in 535 advanced-stage non–small cell lung cancer (NSCLC) patients from two independent cohorts (307 from Nanjing and 228 from Beijing). A replication was carried out on an independent cohort of 340 patients from Southeastern China followed by a second validation on 409 patients from the Massachusetts General Hospital (Boston, MA). RESULTS: Consistent associations with NSCLC survival were identified for five single-nucleotide polymorphisms (SNP) in Chinese populations with P values ranging from 3.63 × 10(−5) to 4.19 × 10(−7) in the additive genetic model. The minor allele of three SNPs (rs7629386 at 3p22.1, rs969088 at 5p14.1, and rs3850370 at 14q24.3) were associated with worse NSCLC survival while 2 (rs41997 at 7q31.31 and rs12000445 at 9p21.3) were associated with better NSCLC survival. In addition, rs7629386 at 3p22.1 (CTNNB1) and rs3850370 at 14q24.3 (SNW1-ALKBH1-NRXN3) were further replicated in the Caucasian population. CONCLUSION: In this three-stage genome-wide association studies, we identified five SNPs as markers for survival of advanced-stage NSCLC patients treated with first-line platinum-based chemotherapy in Chinese Han populations. Two of these SNPs, rs7629386 and rs3850370, could also be markers for survival among Caucasian patients.